Optical filters for stereoscopic image sensors - Maciel, Marino Jesus Correia (2013)
This paper presents optical filters for integration on stereoscopic image sensors. The filters must cover each one of primary colors within the visible, in order to yield a passband around the respective wavelengths. Dielectric materials based on SiO 2 and TiO 2 were used due to their compatibility with silicon. The best simulation with only 3 dielectric layers resulted in optical filters with full width at half maximum (FWHMs) of 79, 95 and 124 nm and central wavelengths of 456, 529 and 605 nm, respectively.